Pengaruh Pendapatan Dan Religiusitas Terhadap Kinerja Karyawan (Studi Pada PT. Bhakti Idola Tama Kecamatan Sungai Gelam Kabupaten Muaro Jambi) - As’ad Isma; Victor Diwantara; Ira Puspita Sari (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
The thesis with the title "The Influence of Income and Religiosity on Employee Performance (Study at PT. Bhakti Idola Tama, Sungai Gelam District, Muaro Jambi Regency)" was written by Ira Puspita Sari, NIM 501190279, Department of Sharia Economics, Sulthan Thaha Saifuddin State Islamic University, Jambi 2023. An employee's performance will increase and develop when the employee is satisfied with the income received and an attitude of religiosity in each employee. The aim of this research is to determine the effect of income and religiosity on employee performance. The research method used in this thesis research is descriptive quantitative. The samples taken were 40 respondents. Data collection techniques by researchers are literature study, observation, interviews and questionnaires. The results of the research in this thesis are that Income and Religiosity simultaneously or together have a positive and significant effect on the performance of PT employees. Bhakti Idol Tama. It is known that the significance value for income and religiosity (X) simultaneously on Employee Performance (Y) is 0.003 < 0.05 and the calculated F value > F table (6.668 > 3.25). So it can be concluded that Ha is accepted and Ho is rejected. It is hoped that the results of this research can contribute, have an impact or have implications for related parties so that they can be used as a reference for research, scientific development and so on.